Characterization and quantification of the pozzolanic reactivity of natural and non-conventional pozzolans. (October 2022) - Yoon, Jinyoung; Jafari, Khashayar; Tokpatayeva, Raikhan; Peethamparan, Sulapha; Olek, Jan; Rajabipour, Farshad
Abstract: High quality pozzolans are needed to produce durable and low CO2 concrete. While extensive literature is available on pozzolanic reactivity and reaction products of conventional fly ash and slag cement, similar information is scarce for natural and non-conventional pozzolans (NNPs), impeding their use in concrete. This study presents a comprehensive evaluation of eleven NNPs, including calcined clays, volcanic ashes, ground bottom ashes, and fluidized bed combustion (FBC) fly ashes. The chemistry, mineralogy, physical properties, and pozzolanic reactivity of these materials were evaluated and benchmarked against conventional pozzolans. Except for one case of high SO3, all NNPs met ASTM C618 specifications as well as RILEM limits of pozzolanic reactivity. Based on ASTM C1897 (the R 3 test), calcined clays were found to be significantly more reactive than fly ash and comparable with slag and silica fume. Volcanic ashes and FBC fly ashes showed similar pozzolanic reactivity to that of Class F fly ash, while ground bottom ashes were comparable with the top 50% of Class F fly ashes. The reaction products of these NNPs were identified using QXRD and thermodynamic modeling as C-A-S-H, mono- and hemi-carboaluminate, monosulfate, and ettringite. Calcined clays formed monosulfate and little to no ettringite while other NNPs formed ettringite but no monosulfate. This was attributed to the availability and dissolution kinetics of alumina versus calcite in the R 3 experiment.